Sustainable highway pavement strategies: Design, construction and maintenance/rehabilitation aspects - Ahmad Kamil, Arshad, Dr. (The Institution of Engineers, Malaysia, 2011)
Link to publisher’s homepage at http://www.myiem.org.my/